Optimum Taxation of Inheritance - Johann K. Brunner; Susanne Pech (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2008)
Inheritances create a second distinguishing characteristic of individuals, in addition to earning abilities. We incorporate this fact into an optimum income taxation model with bequests motivated by joy of giving, and show that a tax on inherited wealth is equivalent to a uniform tax on consumption plus bequests. These taxes are desirable according to an intertemporal social objective if, on average, high-able individuals inherit more wealth than low-able. We demonstrate that such a situation results as the outcome of a process with stochastic transition of abilities over generations, if all descendants are more probable to have their parents ability rank than any other.
Keywords: H21; H24; 330